The Impact of Financial Ratios on Profit Growth in Companies in the Hotel, Restaurant and Tourism Subsector Listed on the Indonesia Stock Exchange During the COVID-19 Pandemic (Period 2019-2021) - Alda Mei Fanesia; Agus Baktiono (NAROTAMA UNIVERSITY, Indonesia, 2023)
This research aims to determine the extent of the influence of the Current Ratio, Net Profit Margin, and Debt to Equity ratio on the growth of earnings in the Hotel, Restaurant, and Tourism sub-sector companies listed on the Indonesia Stock Exchange (BEI) during the period 2019-2021. This research uses a quantitative research method, the technique used in this research is the documentation technique, which is sourced from secondary data, obtained by taking data published by the Indonesia Stock Exchange (BEI). The analysis technique used in this research is multiple linear regression analysis. The significance value for the Current Ratio (CR) variable = (0.013) < (0.05), so the Current Ratio (CR) has a significant effect on earnings growth. The significance value of the Net Profit Margin (NPM) = (2.048) and significance (0.000) < (0.05), so the Net Profit Margin (NPM) has a significant effect on earnings growth. Meanwhile, the Debt equity Ratio (DER) variable + (-2.048) and significance (0.667) > (0.05) so the Debt equity ratio (DER) does not have an effect on earnings growth.